“Troponinosis”, the Cardiologist’s Curse—When Clinic–Laboratory Interaction Unveils the Mystery: A Case Report - Davide Bosi; Simone Canovi; Andrea Pennacchioni; Pierluigi Demola; Mattia Corradini; Vincenzo Guiducci; Rossana Colla; Alessandro Navazio (Journal of Cardiovascular Development and Disease, 2023)
Cardiac troponins are key diagnostic and prognostic biomarkers in acute myocardial infarction and, more generally, for the detection of myocardial injury. Since the introduction of the first immunochemistry methods, there has been a remarkable evolution in analytical performance, especially concerning a progressive improvement in sensitivity. However, the measurement of circulating troponins remains rarely susceptible to analytical interferences. We report a case of persistently elevated troponin I concentrations in a patient with known ischemic heart disease, which almost led to unnecessary diagnostic–therapeutic interventions. A prompt laboratory consultation by the cardiologist ultimately led to the identification of an analytical interference due to troponin macrocomplexes (macrotroponin) causing elevated troponin values in the absence of a clinical presentation compatible with myocardial damage.